Structural Design of a Large-Scale 3D-Printed High-Altitude Propeller: Methodology and Experimental Validation - Ahmed Malim; Nikolaos Mourousias; Benoît G. Marinus; Tim De Troyer (Aerospace, 2023)
This paper presents an original approach to the structural design and analysis of a 3D-printed thermoplastic-core propeller blade for high-altitude UAVs. A macroscale linear isotropic numerical model for the behavior of 3D-printed parts (in Tough PLA, as well as ABS) is fed with values from tensile and bending testing on standard specimens (ISO 527-2/1A and ASTM D5023) before validation by experiments on a representative scaled substitute blade and blade root. The influence of printing parameters, such as material, layer thickness, and raster orientation, is also addressed, as well as variability between prints. To conclude on the validity of the present methodology for complex shapes, a validation of the numerical results with experiments was performed on a scaled 3D-printed twisted blade. The presented macroscale approach to 3D-printed materials was able to predict tensile and bending deformation with good accuracy compared to previously published micro- or meso-scale approaches since it is built from systematic tensile and bending testing on standard specimens to representative blade assemblies. It provides a reliable digital twin for the early design stages of 3D-printed propeller blades. As a proof-of-concept, the validated methodology was then used to design and numerically analyze a large-scale blade using steady one-way Fluid-Structure Interaction in take-off and cruise conditions. The computed stress levels in the blade structure were within safe margins, thereby proving the feasibility of the 3D printing of full-scale propeller blades for high-altitude platforms.